Pengaruh Kinerja Lingkungan, Biaya Lingkungan dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI 2020-2021) - Prinanta, Ledys Juncia; Amin, Moh.; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The responsibility of a company consists of three important aspects, namely financial, social and environmental. The environmental aspect is currently a concern considering its broad impact and related to the sustainability of the earth. Because, there are still many companies that ignore environmental aspects in pursuit of financial aspects so that their environmental performance is still low, including in manufacturing companies whose activities cause a lot of environmental impacts. This study aims to determine 1). influence of environmental performance on financial performance, 2). Effect of environmental costs on financial performance, and 3). Company size on financial performance. Sampling in this study using purposive sampling method. The sample for this research is 100 manufacturing companies listed on the IDX in 2019-2020. The data analysis technique used is multiple linear regression, with descriptive analysis tests, normality tests, classic assumption tests, coefficient determination tests, partial tests and simultaneous tests to determine the relationship between variables. By using the SPSS statistical tool, the results of this study indicate that 1) environmental performance has an effect on financial performance, 2) environmental costs have a negative and significant effect on financial performance, 3) company size has an effect on financial performance.Keywords: Environmental Performance, Environmental Costs, Company Size, Financial Performance